The Effect of Pineapple Peel Extract As a Denture Cleanser on Flexural Strength of Nylon Thermoplastic Denture Base Materials - Paulus Budi Teguh; Oka Lestari; Chaterina Diyah Nanik (Denta Journal Kedokteran Gigi, 2022)
Background: Nylon thermoplastic has been widely used as denture base material because of its esthetic property, high flexibility, and flexural strength. It is very important to maintain the removable dentures’ cleanliness, which is frequently done with the chemical technique by immersing the denture in a solution. The composition of malic acid and citric acid from pineapple peel extract has antibacterial and antifungal properties, so it can be used not only as a denture cleanser but also affect the flexural strength of denture base material. Objective: To determine the effect of pineapple peel extract as a denture cleanser on the flexural strength of nylon thermoplastic denture base material. Method: This is experimental laboratory research with a post-test-only group design using 36 samples, namely 18 Valplast samples and 18 Lucitone FRS measuring 64mm X 10mm X 2.5mm divided into 4 groups (Valplast control, Valplast experiment, Lucitone FRS control, and Lucitone FRS experiment). The samples were treated by immersing them in sterile distilled water as control, and in 3.5% pineapple peel extract for 15 minutes 3 times a day for 10 days as treatment. Flexural strength measurement using Universal Testing Machine. The data obtained were analyzed by the One Way ANOVA test. Result: There was a decrease in flexural strength in the Valplast and Lucitone FRS groups immersed in 3.5% pineapple peel extract. Lucitone FRS groups had higher flexural strength than Valplast’s. Conclusion: There is a decrease in flexural strength of nylon thermoplastic denture base after being immersed in 3.5% pineapple peel extract.